Unique sequence signatures in plant lipolytic enzymes emerging research and opportunities - Halima, Nihed Ben, 1987- (Engineering Science Reference, an imprint of IGI Global, 2019)
"This book addresses the importance of lipases and phospholipases from plants. The focuses on the structural aspects of these enzymes. It also explores insights into their functions and their phylogenetic evolution"--